EXPRESSIVE SPEECH ACTS IN YOUTUBE COMMENTS: A PRAGMATIC ANALYSIS OF PRINCE EA'S VIDEOS - Irawansyah, Irawansyah; Kurniawan, Iwan; Caresta, Vionica Sandra (Indonesian EFL Journal, 2024)
The growing volume of comments from online users expressing their opinions about Prince EA's video's content—which brought up issues with the educational system was the driving force for this study. The expressions used by netizens in the comments section have a certain meaning, and it's critical to grasp this meaning to avoid miscommunication and guarantee clear communication. Pragmatics' expressive speech act theory sheds light on this occurrence. The purposes of this study were to identify the various forms of expressive speech actions that may be found in Prince EA's YouTube channel's comment section and to explain the significance of these acts. The comments from Prince EA's videos were used in this study's descriptive qualitative analysis, "I just sued the school system" and Students Vs. Teacher". Condensing, displaying, and drawing conclusions from the data were all part of the analysis. This research mentioned that seven out of eight expressive speech act kinds in the comment, such as volition, agreement, gratitude, exclamation, greetings, and sorrows. Among these, thanking (gratitude) was the most frequently expressed of them, appearing 36 times in total. Additionally, to explain the meaning of expressive speech acts in the comment section, the researchers first examined the context (the content of two Prince EA'S video). In essence, this research recommends that lecturers can be more careful and wiser in expressing feelings to students through utterances. Thus, a more positive, inclusive environment will be created and can reduce the potential for unwanted misunderstandings between students and lecturers.Keywords: expressive speech act comments; prince EA; Youtube channel.